Evaluasi Kualitas Guru Bimbingan dan Konseling dalam Membantu Perkembangan Siswa di Sekolah - Silvia Hendriyani; Aziz Nurhafidz; Yanneri Elfa Kiswara Rahmantya (UIN Siber Syekh Nurjati Cirebon, 2023)
Improving the quality of guidance and counseling services in schools can be enhanced through the implementation of accountability principles as well as continuous training for counselors to improve their competencies in this field. Continuous training for counselors to improve their competence in this area. In addition, involving parents, students, and the psychological team in the evaluation process can help gather diverse perspectives and improve the effectiveness of services. It is also important to consider the qualifications and experience of school guidance counselors, as well as their level of participation in supervision and professional organizations. In addition, recognizing and highlighting the contributions of school guidance counselors to student well-being and academic achievement can provide a clearer understanding of their role and impact. Active collaboration in a community of support, both among fellow counselors and with other stakeholders, can also enhance therapeutic benefits and learning opportunities during counseling sessions. This study is to determine the quality of Guidance and Counseling teachers in improving student learning success at Vocational High Schools.